Populist Ideology, Policy and the Real Economy: Walking the Stick - Ege Asutay; Christopher Ball; Andreas Freytag (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Populist policies are known to generate a walking stick pattern of high output growth and low inflation followed by low growth and high inflation. Traditionally, researchers viewed this as resulting primarily from populist monetary and fiscal policies that ignore intertemporal budget constraints. We show that this same walking stick pattern can also be driven by real-sector reallocative policies that are a direct manifestation of populist ideology. Using an open economy, monetary Romer (1990) endogenous growth model, we show that the real re-allocation of workers away from jobs perceived as "elite" – here modelled as researchers – to manufacturing industries generates an initial output boom but lowers productivity growth, causing a subsequent decline. In this environment even monetary policy that respects intertemporal budget constraints will generate all the classic, Dornbusch & Edwards (1990), populist patterns: a populist boom-bust output cycle, low-high inflation, and trade deficits. We use the model along with recent political economy research such as Funke et al. (2023) and recent political science contributions to organize the data as well as test its implications with a Two-Way Fixed Effects Model and a Panel Vector Autoregressions (PVAR) on a sample of populist and non-populist governments from the late 20th Century until today. Our empirical results support that the model and its real-policy implications provide useful insights for understanding populism and its macroeconomic effects.
Keywords: E5; E6; H5; 330; populism; economic growth; inflation; populist policies